The application level of governance principles from the perspective of cycle two teachers of basic education schools in Al- Dakhiliya and South Al- Sharqiya governorates in the Sultanate of Oman - Alharrasi, Muslem Salim; Alrasbi, Amina Rashed (Journal of Economic, Administrative and Legal Sciences, 2021)
The present study aimed to identify the application level of governance principles from the point of view of cycle two teachers of basic education schools in the governorates of Al- Dakhiliya and South Al- Sharqiya in the Sultanate of Oman. The study used the descriptive method depending on the questionnaire tool which consist of 29 statements distributed to a sample of 410 teachers from cycle two school in Al Dakhliya and South Al Sharqiya governorate. The results of the study showed that the level of application of the governance principles obtained an overall average (3.71 out of 5), with an application level (high), and at the level of dimensions, the first dimension obtained transparency with the highest average (3.80), then the accountability dimension with an average (3.75), and the two were at a (high) level. While the third was the participation dimension with an average of (3.67), and finally the justice dimension with an average of (3.59), and the two were with the level of application (average). The results also showed that there are no statistically significant differences at the level of significance less than (0.05) between the averages of the estimates of the teachers of the second cycle of basic education schools in the governorates of Al Dakhiliya and South Al Sharqiya in the Sultanate of Oman for the application of governance principles due to variables (years of experience, educational qualification), while there are statistically significant differences at the level of significance less than (0.05) due to variables (gender). In favor of females, and based on the results, the researchers presented a set of recommendations and proposals to improve the level of application of governance principles in schools of the second cycle of basic education in the governorates of Al Dakhiliyah, South Al Sharqiyah and the whole of the Sultanate.
Keywords: governance; basic education; principles of governance